Exploring the attitudes and strategies of peri-urban vegetable growers in the Santiago Metropolitan Region of Chile - Sofía Boza; Marcos Mora; Aracely Nuñez; Macarena Espinoza; Karina Orellana (Economía Agraria y Recursos Naturales, 2022)
Vegetable production is common in peri-urban agriculture where produce is sold in nearby towns, and the Santiago Metropolitan Region (SMR) in Chile is no exception. The objective of this article is to explore the productive, commercial and management strategies of small-scale vegetable growers at the SMR, their attitudes towards their activity, and to identify different profiles. We surveyed in person 170 farmers. The data was analyzed using descriptive and multivariate techniques. Results suggest that different characteristics and strategies are concomitant to certain attitudes that vegetable growers hold towards key aspects such as innovation or willingness to associate.